Case report: Infective endocarditis after transcatheter aortic valve implantation surgically treated with sutureless prosthesis and ascending aorta replacement - Cabrucci, Francesco; Bacchi, Beatrice; Codecasa, Riccardo; Stefàno, Pierluigi (Frontiers in Cardiovascular Medicine, 2023)
Infective endocarditis on transcatheter aortic valve implantation (TAVI) represents an increasingly frequent challenge for cardiac surgeons. Patients undergoing TAVI usually have high mortality risk scores and unsuitable anatomy for the traditional surgical approach. Therefore, surgical planning is crucial, albeit sometimes intraoperative findings can be unexpected and arduous. We describe a case of infective endocarditis on TAVI in a patient with a porcelain aorta and “hostile” aortic root surgically treated with Perceval sutureless prosthesis and ascending aorta replacement.